Digital Marketing, Green Consumerism, and Style Engagement: Understanding Gen Z’s Thrift Shopping Decisions - Putri, Marsanda Dwi; Fietroh, Muhammad Nur (Journal of Educational Management Research, 2025)
This study examines how Social Media Marketing (SMM), Green Consumer Behavior (GCB), and Fashion Involvement (FI) influence Generation Z’s thrifting purchase decisions in Sumbawa Regency. Driven by the rise of the digital economy, growing social media use, and increasing sustainable fashion trends, the research applies an explanatory quantitative method with a cross-sectional design. A purposive sample of 100 Gen Z respondents completed a validated 5-point Likert scale questionnaire. Data were analyzed using multiple linear regression after classical assumption testing. Findings reveal that SMM, GCB, and FI each have a positive and significant effect on thrifting purchase decisions, both individually and collectively. FI emerges as the strongest driver, showing that passion, interest, and engagement in fashion most strongly shape buying behavior. SMM enhances product awareness and fosters interactive relationships, while GCB motivates eco-conscious choices. These insights offer strategic value for thrifting businesses in non-metropolitan areas: leverage digital platforms for targeted engagement, promote sustainability narratives, and align product offerings with evolving youth fashion trends.